Predicting adherence with the Glaucoma Treatment Compliance Assessment Tool - Sanchez, Facundo G (J Glaucoma, 2020)
PURPOSE: To determine the health behavior factors related to glaucoma adherence in patients with self-reported poor adherence. METHODS: A research coordinator used the Chang Adherence Measure and the Morisky Medication Adherence Scale to identify subjects with poor self-reported glaucoma medication adherence, and enrolled them in a three-month study to electronically monitor medication adherence. At enrollment, the coordinator administered the Glaucoma Treatment Compliance Assessment Tool (GTCAT). We calculated the percentage of prescribed doses taken over a 3-month period using an electronic dose monitor (AdhereTech, New York, NY). We used Rasch analysis, and univariate and multivariable regression to determine the GTCAT statements that predicted electronically monitored adherence. RESULTS: The mean adherence was 73.8% (SD 21.04, range 13–100). Rasch analysis showed that the GTCAT had a good overall fit and no differential bias (Anderson Likelihood Ratio (LR) test >.05). Multiple GTCAT statements were associated with adherence, which represented increased knowledge, increased cues-to-action, decreased barriers, less depression, and increased self-efficacy (p<.09 for each). The full GTCAT or a subset of statements had a high association with adherence (Rsq range 0.44-.51, p<.005 for all). The GTCAT identified more than 50% of patients who wanted more education about glaucoma; more than 68% who did not use reminders; and more than 40% who reported having difficulty using the eye drops. CONCLUSIONS: The GTCAT identified multiple factors associated with adherence. Clinicians and researchers could use this tool to identify specific barriers to adherence and develop potential interventions to improve adherence.